Implementasi Kebijakan Gerakan Kembali Bersekolah: Analisis Model Grindle dalam Penanganan Anak Tidak Sekolah di Kabupaten Brebes - Hakim, Lukmanul; Izzatusholekha, Izzatusholekha; Puspita Dewi, Maya; Rudiatin, Endang (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
This study aims to analyze the implementation of the GKB in fulfilling children's rights in Brebes district. This analysis uses Merilee S. Grindle's theory with implementation content indicators including: Power, interest and strategy of actor involved, Institution an regime characteristic and Compliance and responsiveness. The data sources used in this research came from observations, interviews and documentation studies. The results of this study found that stakeholders have an important role in the GKB program, namely issuing regulations and monitoring the implementation of the regulation.